Total Synthesis of Daphniphyllum Alkaloids: (+)-Daphlongamine E, (+)-Calyciphylline R, and (–)-10-Deoxydaphnipaxianine A - Zhang, Yan; Chen, Yuye; Xu, Jing (Synthesis, 2024)
Here, we wish to describe our detailed efforts in the total synthesis of three calyciphylline A-type alkaloids, namely (+)-daphlongamine E, (+)-calyciphylline R, and (–)-10-deoxydaphnipaxianine A. Important steps in our approach include a Pt-catalyzed nitrile hydration, a Babler–Dauben rearrangement, a novel selective amide reduction tactic, and an oxidative Nazarov cyclization via an unfunctionalized tertiary divinyl carbinol (TDC).
Keywords: Daphniphyllum alkaloids; total synthesis; oxidative Nazarov cyclization; Babler–Dauben rearrangement; amide reduction; nitrile hydration